Inclusive Leadership in Romanian Schools - Daniela Ionescu; Vrăsmaș Ecaterina (Babes-Bolyai University, 2023)
One of the 17 Sustainable Development Goals (SDGs), informally reunited under the name of Global Goals 2030, is Quality Education - Guaranteeing quality education and promoting lifelong learning opportunities for all. Our society has reached the stage where quality education is no longer a privilege of a few, but a fundamental right. Therefore, failure to achieve quality education is tantamount to not having had the opportunity to grow and develop as fully as in a free and just society, in an inclusive perspective. The objective of this study is to apply the tool "Inclusive leadership in schools" for the Romanian context. The methods used are the validity of the content by expert judgement; validity of construction through exploratory analysis and factorial confirmation; and reliability by Cronbach alpha coefficient and half-life method. The results show that both the school leadership and teacher version and the family version have optimal levels of validity and reliability for measuring inclusive leadership in Romanian schools. The results suggest that inclusive leadership is expected to work most closely through their influence on the development, improvement of the quality of teaching and learning, and on promoting an enabling school climate and culture with an emphasis on high opportunities and quality education.